2010
DOI: 10.1159/000322581
|View full text |Cite
|
Sign up to set email alerts
|

Low Triiodothyronine Alters Flow-Mediated Vasodilatation in Advanced Nondiabetic Kidney Disease

Abstract: Background/Aims: Subclinical or frank hypothyroidism is causally implicated in endothelial dysfunction. Since the plasma concentration of the active form of thyroid hormone, triiodothyronine (T3), is reduced in chronic kidney disease (CKD), where endothelial function is frequently altered, low T3 may be a factor implicated in this disturbance in CKD patients. Methods: We investigated the relationship between flow-mediated vasodilatation (FMD) and thyroid hormones in a series of 217 nondia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 51 publications
3
39
0
Order By: Relevance
“…In support of the association between T3 and cardiovascular death in our study, a previous report (11) in patients with moderate to severe kidney disease reported that T3 levels inversely associated with flow-mediated vasodilation and that this observation was dependent on multivariate adjustment for asymmetric dimethylarginine levels. At a cardiac level, low T3 levels in CKD patients are associated with reduced left ventricular function, increased left ventricular mass (13), and elevated intimamedia thickness (12).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In support of the association between T3 and cardiovascular death in our study, a previous report (11) in patients with moderate to severe kidney disease reported that T3 levels inversely associated with flow-mediated vasodilation and that this observation was dependent on multivariate adjustment for asymmetric dimethylarginine levels. At a cardiac level, low T3 levels in CKD patients are associated with reduced left ventricular function, increased left ventricular mass (13), and elevated intimamedia thickness (12).…”
Section: Discussionsupporting
confidence: 89%
“…However, growing evidence suggests participation of T3 in the pathophysiology of endothelial dysfunction (11), atherosclerosis (12), and cardiac abnormalities (13) of CKD patients. Some studies, with somewhat conflicting results, have also implicated thyroid alterations in the mortality risk of CKD patients (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that serum free-T3 (fT3) level associated with impaired endothelial function as assessed by flowmediated dilation in nondiabetic nondialyzed patients with chronic kidney disease (CKD) (17). It is presently unknown whether atherosclerotic features commonly found in dialysis stages are associated with low T3 levels.…”
Section: Introductionmentioning
confidence: 99%
“…T3 is a potent stimulus for NO-dependent vasodilatation in the forearm in healthy subjects. It has also been shown that there is an association between low fT3 levels and endothelial dysfunction in stage 3-4 chronic kidney disease patients 13) . We also observed a significant relationship between the fT3 levels and FMD in our study; which supports that fT3 affects the endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Tatar et al recently demonstrated that low fT3 levels are associated with carotid atherosclerosis in HD patients 11,12) . Yilmaz et al demonstrated a relationship between low fT3 levels and endothelial dysfunction in patients suffering from renal failure 13) . Moreover, there is a well-accepted association between low fT3 levels and mortality in patients suffering from renal failure 14) .…”
Section: Biochemical Measurementsmentioning
confidence: 99%